Revealing Problems on Teaching English for Young Learners at Al – Azhar 55 Islamic Primary School Yogyakarta and How to Solve Them - Widodo, Anang; Dewi, Septi Riana (Jurnal VARIDIKA, 2018)
The present paper aims to reveal the problems faced by teachers when teaching English for second – grade students at Al – Azhar 55 Islamic Primary Schoolin Yogyakarta. This bilingual school is considered as a pilot project which began theprogram in July 2016. There are only 2 classes which are the first and second grade.However, this study involved 21 second-grade students, 2 homeroom teachers, and 1native speaker. Qualitative method was applied in this study by combining documentanalysis, observation, and interview both students and the teachers. The results showsome problems occurred during teaching and learning process and how the teachersovercome them. The problems were (1) students’ lack of discipline during teaching andlearning process (2) the variety of students’ English ability, (3) difficulty in creating habit to use English as daily language, and (4) less support from parents. While, the solutions were (1) applying Class Dojo application, (2) providing the preparation class, (3) support and assistance from teachers and friends, and (4) hands – on learning.